Calculation of sound power of aircraft engine compressor - Терещенко, Юрий Матвеевич; Дорошенко, Екатерина Викторовна; Марковская, Любовь Георгиевна; Политовский, Василий Юстинович (Eastern-European Journal of Enterprise Technologies, 2009)
A comparative analysis of methods for calculating the sound power level of air compressor motor is conducted. With these methods we can calculate the dependence of acoustic power level discrete components compressor from its geometrical and operational parameters, to investigate the noise generation process